El incendio del 17 de abril de 2003 en Chillogallo (Quito) - Jairo Estacio (Bulletin de l'Institut Français d'Études Andines, 2009)
Much of the transport and fuel storage infrastructure is concentrated in the Quito Metropolitan District (DMQ). This situation reflects industrial development policies that were implemented in Ecuador since the 1970s. Many of these facilities were gradually surrounded by an increasingly dense urbanization. For this reason, a potential danger to the population has been created and is highlighted in this essay. This potencial threat was materialized with the fire that occurred in 2003, following the breaking of a pipeline carrying gasoline. The pipeline crosses two poor neighborhoods —El Tránsito and Girón de Chillogallo—, located south of Quito. This accident was the cause of significant human and material damage. It was considered as one of the most serious accidents, involved in transporting fuel, that has occurred in Quito. The event has highlighted weaknesses in both the field of prevention and in crisis management. It also provided experience and lessons in terms of knowledge and management in the field of technological risk, subjects which were poorly known and had not been prioritized in the DMQ.